Descemet Membrane Endothelial Keratoplasty in Vascularized Eyes: Outcome and Effect on Corneal Neovascularization. Issue 6 (June 2021) - Hayashi, Takahiko; Zhang, Wei; Hos, Deniz; Schrittenlocher, Silvia; Nhat Hung Le, Viet; Siebelmann, Sebastian; Matthaei, Mario; Bock, Felix; Bachmann, Björn; Cursiefen, Claus
Abstract : Purpose: To report the outcomes after Descemet membrane endothelial keratoplasty (DMEK) in vascularized eyes. Methods: Consecutive cases of DMEK in vascularized eyes (involving ≥2 vascularized quadrants) were selected from a prospective database. Best corrected visual acuity, endothelial cell density (ECD), central corneal thickness, corneal transplant rejection episode, graft survival, and area of neovascularization (quantified using image analysis software) were evaluated. Results: In this study, 24 eyes of 24 patients were selected [mean age, 65.0 years; mean follow-up duration, 14.8 months (6–36 months)], which consists of 14 vascularized eyes after failed penetrating keratoplasty and 10 vascularized eyes with bullous keratopathy. Best corrected visual acuity improved from 1.60 ± 1.02 LogMAR preoperatively to 0.47 ± 0.37 LogMAR 12 months postoperatively ( P < 0.001). Central corneal thickness decreased from 824 ± 193 μm preoperatively to 544 ± 48 μm 12 months postoperatively ( P = 0.001). The donor ECD decreased from 2272 ± 723 cells/mm 2 preoperatively to 1570 ± 279 cells/mm 2 12 months postoperatively. The total loss of ECD at the last visit was 40.7% ± 13.0%. Eight of 24 eyes (33.3%) required rebubbling, which resulted in final attachment. The corneal neovascularization area significantly regressed from 4.68% ± 3.26% preoperatively to 2.28% ± 1.58% (n = 18, P = 0.021). Corneal transplant rejection episodes occurred in 1 eye of 24 patients (4.2%). There was no primary graft failure. Conclusions: DMEK is a feasible option to treat endothelial dysfunction in vascularized eyes. Abstract : Supplemental Digital Content is Available in the Text.